What innovation policies for ecological transition? Powering the green innovation machine - Reinhilde Veugelers (WWWforEurope, 2014)
In this contribution we describe how green policies should be designed to activate private innovation forces for ecological transitions. We look at the evidence on the current deployment of green policies and the current performance of the private green innovation machine. We try to assess how strong which types of government interventions have and can be to power the green innovation machine. An important insight from the economic analysis of the effectiveness of the public intervention for green innovations, is the complementarity between policy instruments, requiring an adequate policy mix of instruments, rather than a focus on individual instruments. The evidence provides little support for the efficacy of single instruments, like subsidies, when used in isolation. For the EU, this is perhaps the biggest challenge for its green technology policy: the lack of a sufficiently high carbon price. And as the evidence has shown that the world of green science and technologies is an emerging global, multipolar one, with many geographically dispersed sources in the various green scientific fields and technologies, coordination of green policies internationally should therefore be high on the policy agenda.
Keywords: O31; O38; 330; Ecological innovation; Economic growth path; Globalisation; Green jobs; Innovation; Innovation policy; New technologies; Patents; Policy options; Research; Socio-ecological transition